Effect of irrigation and nitrogen on water use, moisture extraction pattern, nitrogen uptake and yield of coriander (Coriandrum sativum L.) in north-western irrigated plains of Rajasthan - S M Kumawat, S R Bhunia, S D Ratnoo (Journal of Spices and Aromatic Crops, 2009)
An experiment was conducted at Sriganganagar (Rajasthan) to study water use, water useefficiency, nitrogen uptake, yield and economics of coriander (Coriandrum sativum) cultivars(RCr 41, RCr 435) under various levels of nitrogen (20, 40 and 60 kg ha-1) and irrigation (IW/CPE ratios 0.6, 0.8 and irrigation at branching + flowering + seed formation stages). Thehighest seed yield (10.98 q ha-1), yield attributes and benefit: cost ratio (2.65) were recordedwith 60 kg nitrogen ha-1. Increasing levels of nitrogen also recorded higher consumptive useof water and nitrogen uptake. Plants under higher levels of nitrogen (60 kg ha-1) extractedmore water from the lower depth (60-90 cm) than lower level of nitrogen (20 kg ha-1). Increasein irrigation frequency significantly enhanced the yield and yield attributes of both thecultivars. Similarly, water use, nitrogen uptake and benefit:cost ratio were also higher withhigher levels of irrigation.